Efficacy and safety of esketamine for pain control after cesarean delivery: a systematic review and meta-analysis of randomized controlled trials - Jiang, Tingyu; Zhao, Rui (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to investigate the efficacy and safety of esketamine in reducing postpartum pain and depression in patients undergoing cesarean delivery (CD).MethodsWeb of Science, Embase, PubMed, and Cochrane Library were searched from the inception of each database up to September 2025 to select relevant studies. Randomized controlled trials (RCTs) that assessed the efficacy of esketamine for pain control in patients undergoing CD were selected. The outcomes included scores of postpartum pain, the incidence of depression after surgery, scores on the Edinburgh Postnatal Depression Scale, and the incidence of adverse events before and after surgery. The stability of the results and potential sources of heterogeneity were investigated by subgroup and sensitivity analyses.ResultsThis meta-analysis included ten studies comprising 15 intervention groups. A total of 2218 individuals undergoing CD were involved. Compared with the control group, esketamine showed relatively favorable effects on controlling rest pain at 24 h (SMD = −0.42; 95% CI: −0.69 to −0.16; P < 0.00001; I2 = 84%), movement-evoked pain (MEP) at 24 h (SMD = −0.68; 95% CI: −1.29 to −0.07; P < 0.00001; I2 = 92%), rest pain at 48 h (SMD = −0.22; 95% CI: −0.38 to −0.06; P = 0.006; I2 = 54%), and MEP at 48 h (SMD = −0.63; 95% CI: −1.07 to −0.20; P < 0.00001; I2 = 85%). In contrast to the control group, EPDS scores in the esketamine group were lower (SMD = −0.21; 95% CI: −0.39 to −0.04; P = 0.02; I2 = 45%). Subgroup analyses indicated that pregnant women aged over 30 years who received esketamine had a higher incidence of dizziness (RR = 2.08; 95% CI: 1.26 to 3.34; P = 0.004; I2 = 64%). The quality of evidence was moderate for six outcomes, and low for three outcomes according to the GRADE assessment.ConclusionAs a therapy for postoperative analgesia, esketamine shows relatively favorable efficacy in pain control and is associated with a lower risk of postpartum depression. However, this result is unstable. Furthermore, esketamine may increase the risk of dizziness in pregnant women aged over 30 years. Since all the experiments in this study are conducted in China, there are certain regional limitations.